Dynamic Vehicular Traffic Load: Definition and Quantification - Ostermayer, Gerald; Backfrieder, Christian; Lindorfer, Manuel (Journal of Telecommunications and the Digital Economy, 2019)
In this paper, we introduce a method that quantifies the amount of traffic over time by the help of a cloud calculation service and vehicular communication. Furthermore, the approach is applicable also in vehicular traffic simulations, which are widely used in research to demonstrate the effects of proposed solutions to traffic problems. As unused road segments strongly influence the overall traffic load (i.e. used vs full road capacity), we propose a methodology that dynamically calculates the load over time and considers whether specific parts of the road network are used. We introduce two possibilities to filter out distortion of the created statistics due to variation in usage over time. Our novel approach is both simple but widely configurable to fit individual needs. The approach is proven by simulations and application of the load calculation in combination with an intelligent route optimization approach by comparing the optimization gain with the calculated traffic load.